(untitled) (Journal of Partial Differential Equations, 2015)
" This article is devoted to study the existence of renormalized solutions for the nonlinear p(x)-parabolic problemin the Weighted-Variable-Exponent Sobolev spaces, without the sign condition and the coercivity condition."